Assisting the Enhancement of Students’ Reading Interest through Teaching Assistance Activities at SMKN 08 Pinrang - Syafiqah Syafiqah; Muh Irwan; Pratiwi Ramlan; Anasruddin Anasruddin; Wijaya Wijaya; Farahdita Aprilia; Rasmi Rasmi; Alfiyyah Nurhafanah; Debiyanti Debiyanti (Universitas Muhammadiyah Enrekang, 2024)
The community service program at SMKN 8 Pinrang was conducted through the Teaching Assistance Program (PKKM), aiming to enhance students' reading interest and foster a strong literacy culture. This activity aligns with the Three Pillars of Higher Education (Tri Dharma Perguruan Tinggi) and provides students with a valuable opportunity to gain both learning and working experiences through teaching assistance at SMKN 8 Pinrang.Based on an assessment of student literacy at SMKN 8 Pinrang, the program leveraged the potential to refine and develop students' reading interests. The teaching assistance program was fully supported by the university and supervised by field advisors. Reading interest activities were carried out through wall magazines, short story and numeracy competitions, and engaging activities tailored to subject-based ice-breaking sessions.The results of this program demonstrated an increase in students' literacy and reading interest, highlighting the significant role of university students in teaching assistance. They not only motivated students to learn but also supported teachers in fulfilling their responsibilities effectively